2015
DOI: 10.1039/c4ra13272f
|View full text |Cite
|
Sign up to set email alerts
|

A green and one-pot synthesis of benzo[g]chromene derivatives through a multi-component reaction catalyzed by lipase

Abstract: The synthesis of benzo[g]chromene derivatives through a multi-component reaction catalyzed by lipase was reported in the first time. This novel efficient method has the advantages of environmental friendliness, high yield and simple work-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…These results indicated that salicylaldehyde might be reacted with malononitrile which binds to the oxyanion hole in the lipase firstly. The catalytic proficiency ((k app cat /K app M )/k non 35 was much lower than 10 8 which demonstrated that the substrates in this reaction was not the native substrates of lipase [34]. According to the previous reports [32 -36], lipase can catalyze the Michael addition and Knoevenagel condensation in the domino reactions.…”
Section: Scheme 1 Lipase-catalyzed Condensation Of Substituted Salicymentioning
confidence: 78%
See 2 more Smart Citations
“…These results indicated that salicylaldehyde might be reacted with malononitrile which binds to the oxyanion hole in the lipase firstly. The catalytic proficiency ((k app cat /K app M )/k non 35 was much lower than 10 8 which demonstrated that the substrates in this reaction was not the native substrates of lipase [34]. According to the previous reports [32 -36], lipase can catalyze the Michael addition and Knoevenagel condensation in the domino reactions.…”
Section: Scheme 1 Lipase-catalyzed Condensation Of Substituted Salicymentioning
confidence: 78%
“…2- 35 Iminochromene appears as a ubiquitous structural motif in many heterocyclic compounds. Synthetic analogues were developed over the years, some of them displaying extensive bioactivities, such as antifungal and antimicrobial activity [22][23].…”
Section: Yield Short Reaction Time and Environmental Friendlinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the synthesis of benzo[ g ]chromenes has been described through a three‐component reaction, which involved the use of stoichiometric amounts of an aromatic aldehyde, malononitrile and 2‐hydroxy‐1,4‐naphthoquinone . After a reaction optimization study, ethanol, 55°C and Candida sp.…”
Section: Hydrolases In Multicomponent and Tandem Nonconventional Reacmentioning
confidence: 99%
“…Exploiting enzyme catalytic promiscuity provides new catalytic tools especially for multicomponent reactions (MCRs). These one‐pot reactions allow the creation of several bonds in one step with excellent chemical yields, reduction in reaction times and waste, toward the access to biologically important compounds [19]. Many reactions were successfully revisited, such as the Mannich reaction,[20] Morita‐Baylis‐Hillman reaction,[21] Knoevenagel reaction,[22] Henry reaction,[23] Michael addition,[24] and aldolization reaction [17e]…”
Section: Introductionmentioning
confidence: 99%